Debates in science education - Watts, Mike (Abingdon, Oxon : Routledge, Taylor & Francis Group, 2014)
'Debates in Science Education explores and highlights the key issues and debates important in science teaching and which trainee, induction-year and early-career teachers will need to address throughout their professional lives. The debates presented will encourage such teachers to consider and reflect on issues relevant to science education in order to reach their own informed judgements, so that they can better understand the field and can situate their own professional work within a broader context. A team of international authors locate their positions in debates by reference to, or interrogation of, counter arguments, and by providing commentaries on further relevant reading in selective, but carefully annotated, bibliographies'--
Includes bibliographical references and index.
Keywords: Science -- Study and teaching; Science teachers -- In-service training